THE POSTOPERATIVE OPIOID ANALGESIA AND BIOPSYCHOSOCIAL MODEL OF PAIN - A. L. Potapov (Вестник анестезиологии и реаниматологии)
The objective of the work is to assess the implementation advisability of the biopsychosocial model of pain during the postoperative opioid analgesia. It was established that under the similar interventions in terms of severity and medication doses the bodily pain with the patients vary by a wide margin. The diagnosed differences may be conditional upon the biological, psychological and social factors, so the biopsychosocial approach is the promising direction to improve the postoperative opioid analgesia efficiency.